2001
DOI: 10.1038/sj.mn.7800079
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Dysfunction Induced by AGE is Mediated by VEGF via Mechanisms Involving Reactive Oxygen Species, Guanylate Cyclase, and Protein Kinase C

Abstract: These observations indicate potentially important roles for oxygen free-radicals and nitric oxide in mediating permeability and blood flow changes induced by glycated proteins via mechanisms involving increased protein kinase C activity and VEGF production. Striking similarities in the mechanism by which hyperglycemia and glycated proteins induce vascular dysfunction suggest that a common pathway mediates effects of these different metabolic imbalances on vascular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 58 publications
(61 reference statements)
2
15
0
Order By: Relevance
“…To the best of our knowledge, this is the first report showing that AGEs induce PKC-b activation in retinal endothelial cells. These findings together with previous results, which show that PKC-b activation is associated with increased endothelial permeability [21] and retinal dysfunction in diabetic animals [22,23], support a key role for the activation of this PKC isoform in abnormal retinal haemodynamics associated with diabetes. It has been proposed that some of the PKC activation in the diabetic retina could be the result of excessive oxidative stress.…”
Section: Discussionsupporting
confidence: 87%
“…To the best of our knowledge, this is the first report showing that AGEs induce PKC-b activation in retinal endothelial cells. These findings together with previous results, which show that PKC-b activation is associated with increased endothelial permeability [21] and retinal dysfunction in diabetic animals [22,23], support a key role for the activation of this PKC isoform in abnormal retinal haemodynamics associated with diabetes. It has been proposed that some of the PKC activation in the diabetic retina could be the result of excessive oxidative stress.…”
Section: Discussionsupporting
confidence: 87%
“…Chronic hyperglycemia associated with diabetes not only decreases bone metabolism but also increases secretion of proinflammatory cytokines such as interleukin 1 (14,15), tumor necrosis factor-a (15)(16)(17) and prostaglandin E 2 (18). Furthermore, it is also reported that hyperglycemia can induce periodontal tissue destruction associated with the formation of advanced glycation end products (15,19,20), vascular dysfunction (21), altered immune function (22) and decreased collagen synthesis (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…9 It has been demonstrated that upregulated oxidative stress promotes vascular dysfunction, lipid peroxidation and glycooxidative molecule production in diabetes. [10][11][12] Enhanced superoxide production has been found in renal cortex from streptozotocin-induced diabetic rats. 13 Thus, it is a reasonable implication and believed that O2 -, as a primary signalling molecule, promotes the production of reactive oxygen species (ROS) downstream, which act as signalling molecules further to cause diabetic nephropathy through a redox-sensitive pathway.…”
mentioning
confidence: 98%